EFFECT OF FOOT MASSAGE ON REDUCING FATIGUE IN PATIENTS UNDERGOING HEMODIALYSIS - Lestari, Yuni Sri; Hudiyawati, Dian (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Hemodialysis can cause various problems, both physical and psychological. One of the physical problems is fatigue, about 71.0%-92.2% of patients undergoing dialysis are exhausted. One therapy to overcome fatigue is foot massage therapy. Purpose: This literature aims to identify the effectiveness of foot massage on the reduction of fatigue in hemodialysis patients. Review: This is a literature study that uses the Pubmed, ProQuest, ScienceDirect and Google Scholar databases (with keywords and article criteria defined by the author). The results of the literature found 4 papers were discussing the effect of foot massage on the reduction of fatigue in hemodialysis patients. Foot massage can improve blood circulation and stimulate the production of endorphins, reducing fatigue, relieving tension, and increasing comfort in hemodialysis patients. Conclusion: The four papers show that foot massage was effective on reducing fatigue in hemodialysis patients